\(a)\) Ta có :
\(M=a^3+b^3=\left(a+b\right)\left(a^2+b^2-ab\right)\)
Thay \(a+b=1\) vào \(M=\left(a+b\right)\left(a^2+b^2-ab\right)\) ta được :
\(M=\left(a+b\right)\left(a^2+b^2-ab\right)=1\left(a^2+b^2-ab\right)=a^2+b^2-ab\)
Lại có :
\(a^2\ge0\)
\(b^2\ge0\)
\(\Rightarrow\)\(a^2+b^2\ge0\)
\(\Rightarrow\)\(a^2+b^2-ab\ge-ab\)
Dấu "=" xảy ra khi \(\hept{\begin{cases}a^2=0\\b^2=0\end{cases}\Leftrightarrow\hept{\begin{cases}a=0\\b=0\end{cases}}}\)
Vậy \(M_{min}=-ab\) khi \(a=b=0\)
Sai thì thôi nhé, mk mới lớp 7
dytt me dễ vãi lone
\(a^3+\frac{1}{8}+\frac{1}{8}\ge3\sqrt[3]{\frac{a^3.1}{8.8}}=\frac{3}{4}a.\)
\(b^3+\frac{1}{8}+\frac{1}{8}\ge\frac{3}{4}b\)
\(M+\frac{4}{8}\ge\frac{3}{4}\left(a+b\right)=\frac{3}{4}\Leftrightarrow M\ge\frac{3}{4}-\frac{4}{8}=?\) tự tính dcmmm
b.
\(a^3+1+1\ge3\sqrt[3]{a^3}=3a\)
\(b^3+1+1\ge3b\)
\(a^3+b^3+4\ge3\left(A+b\right)\)
cái dmcmmm a^3+b^3=2 suy ra
\(6\ge3\left(a+b\right)\)
\(2\ge a+b\)
dytt cụ m tự kết luận